Pakistan-Russia Relations: The Afghanistan Factor - Aman Ullah; Noor Fatima, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
Historically, Afghanistan has had a deep impact on Pakistan-Russia relations, though not positive. The prevalent geopolitical realities also suggest that Moscow and Islamabad have multiple avenues of cooperation for mutual benefits. The two countries have various similarities of interest vis a vis Afghanistan, which necessitate bilateral cooperation. The study elucidates the importance of Afghanistan in Pak-Russia bilateral relations. Both states have a couple of shared objectives vis a vis Afghanistan such as elimination of terrorism and extremism, end to violence, control of narcotics smuggling and promotion of regional connectivity. Realist theory provides an appropriate framework to conduct this study that also entails discussion on Russia’s pursuit for maximization of power. After the US withdrawal from Afghanistan, the war ravaged country had been facing critical situation with impending humanitarian crisis caused by shortage of food and medicine, recognition of the current Taliban government by the world and economic meltdown. Both Pakistan and Russia had appealed the world to stay engaged with the new Taliban government to avert humanitarian crisis. While Pakistan’s historical alliance with the United States and Russia’s traditional strong ties with India had been important factors in Pakistan-Russia ties, Afghanistan factor appeared to be a dominant factor.